Methods of simultaneous preparation of various active substances from Stichopus chloronotus and functional evaluation of active substances. Issue 1 (31st December 2022) - Xia, Yu; Wang, Changwei; Yu, Dejun; Hou, Hu
ABSTRACT : Stichopus chloronotus, a marine sea cucumber rich in n-3 PUFAs and phenolic compounds, is a deep black–green sea cucumber with yellow/ red papillae tips, which has important economic and ecological value. In this project, a process was established to simultaneous extract and prepare four different active substances (including sea cucumber polysaccharide, polypeptide, saponin and lipid) from Stichopus chloronotus . The yields and purity were also improved. Except for polysaccharides, the purity of the other three active substances was above 90%. The extraction rates were all above 60%. In addition, the functional activity of sea cucumber peptides was evaluated. The results showed that sea cucumber peptides could reduce triglyceride content in mice serum, increase glutathione content and relieve alcohol-induced liver damage. The technical research laid a technical foundation for the high value utilization of Stichopus chloronotus .